Análisis y Evaluación Económica-Financiera de la empresa comercial LEXXUZ & CÍA de la Ciudad de Loja, período 2013-2014 - Agila Sepa, Yanina Susana (2016)
The thesis entitled "Analysis and Evaluation of Economic and Financial Lexxuz & Co. trading company., In the city of Loja, period 2013-2014" was held in order to identify whether the management carried out within the company has allowed take adequate precautions for the use of its resources, for it developed the vertical and horizontal analysis to meet both economic and financial structure of the company, thus establishing the degree of percentage share of assets, liabilities, equity, income decisions and Expenses; as well as to know the absolute and relative variation that each item has one year to another. To comply with the specific objective: To apply and interpret financial indicators to measure the degree of liquidity, profitability, activity and indebtedness of the company during the periods analyzed own financial indicators of business activity was applied with their respective interpretations and graphs in order to determine the degree of liquidity, activity, indebtedness and profitability in the periods analyzed. In the second specific objective: To evaluate the economic structure of the company by applying methods such as working capital, cash conversion cycle, Breakeven, Added (EVA) Economic Value, and Dupont System; data and values contained in the financial statements to 6 understand the importance existing between the generated return on investment, asset turnover, the profit margin obtained were taken; leverage and balance that must reach your income and expenses not to lose or win. To fulfill the ultimate goal. To design and submit a report to the Lexxuz & Co. trading company, about Financial Analysis and Evaluation thereof containing conclusions and recommendations, it was necessary to make the whole process I practice as vertical analysis, horizontal, reasons financial and financial evaluation methods in order to get the results, thereby determining each of the conclusions that were reached with appropriate improvement strategies that will be subsequently communicated to the manager so you can make the right decisions. Finally it can be concluded that the trading company Lexxuz & Cia., Does not have an analysis and economic and financial assessment to help you identify whether the use of its resources has been adequate, the utility company is minimal due to the decrease in their sales and the presence of high administrative costs for the adequacy of its business premises that annually, debt has short and long-term financial institutions that will produce considerable capital cost for the high interest payments.